Pelatihan Pemasaran Karya Musik Daerah di Era Digital Pada di Komunitas Siapa Kita Labuan Bajo - Hanny Wadhi, Yohanes Paulus; Siagian, Reynaldo Angga; Asroni, Ondi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Regional Music Marketing Training in the Digital Age On Who We Are Labuan Bajo Community This Community Service Activity Program is a community empowerment program through increasing human resources capacity, especially music marketing in the Labuan Bajo area as a tourist destination (DTW) in West Manggarai Regency, Flores, East Nusa Tenggara. This activity involves teaching staff from various cross-study programs, International Marketing Management and Information Technology. The method used is to practice publishing folk song works on music publisher websites, making good artwork and creating good video content. The result is that participants have a better understanding of how to work with music publishers, how to make good artwork and create good music video content to meet the standards of music publishers and be acceptable to the audience.